2006
DOI: 10.1093/ndt/gfl041
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic conditions stimulate the production of angiogenin and vascular endothelial growth factor by human renal proximal tubular epithelial cells in culture

Abstract: Under hypoxic conditions, the ANG and VEGF secreted by PTEC may modulate angiogenesis and vascular remodeling in the renal interstitium via an increase in the production of HIF-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 16 publications
6
44
0
1
Order By: Relevance
“…According to these findings, an absolute increase in capillary density takes place in hypothyroid hearts, which may result from an increased cardiac production of angiogenic factors (bFGF and HIF-1a), as observed in bradycardia . By contrast, plasma angiogenin, one of the most potent angiogenic factors (Nakamura et al 2006), was markedly reduced in hypothyroid rats. This decrease, together with the vasoconstriction secondary to reduced metabolic needs (Liu et al 2010), may participate in reducing the number of blood vessels in the mesenteric vascular bed.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to these findings, an absolute increase in capillary density takes place in hypothyroid hearts, which may result from an increased cardiac production of angiogenic factors (bFGF and HIF-1a), as observed in bradycardia . By contrast, plasma angiogenin, one of the most potent angiogenic factors (Nakamura et al 2006), was markedly reduced in hypothyroid rats. This decrease, together with the vasoconstriction secondary to reduced metabolic needs (Liu et al 2010), may participate in reducing the number of blood vessels in the mesenteric vascular bed.…”
Section: Discussionmentioning
confidence: 78%
“…The recognised angiogenic factors (Fett et al 1985, Risau & Flamme 1995, Nakamura et al 2006) VEGF and angiogenin were measured in plasma and all these factors plus HIF-1a in the heart and kidney. Hearts and kidneys were homogenised in 50 mm HCl-Tris (pH 7.4) containing 1% Triton X-100 and centrifuged for 15 min at 1000 g. VEGF was analysed by Luminex x-MAP technology with a kit purchased from Millipore (Billerica, MA, USA), while bFGF, angiogenin and HIF-1a were measured by ELISA with kits purchased from Cusabio (Wuhan, China).…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…28,29 However, the cleavage of intact tRNA by angiogenin does not result from a simple upregulation of angiogenin ( Figure 3B). The knockout of Ang1 also did not affect the immunostaining by anti-m1A antibody in the damaged tissue ( Figure 2E).…”
Section: Conformational Change Of Trna Is a Stress Sensormentioning
confidence: 92%
“…However, it has been shown that accumulation of ANG in the nucleolus of target endothelial cells is essential for its biological activity (23,24) and that ANG binds to a receptor on the surface of endothelial cells (25,26) and induces a variety of activities required for angiogenesis (26)(27)(28). ANG has been shown to be upregulated by hypoxia in cultured melanoma cells (29) and in human renal proximal tubular epithelial cells (30).…”
mentioning
confidence: 99%